Peran Shunt Ventrikuloperitoneal dalam Strategi Pengobatan Hidrosefalus Pada Anak : Literature Review - Sari, Indah Purnama; Roro Rukmi Windi Perdani; Diana Mayasari; Intanri Kurniati; Fidha Ramayani; Rizki Hanriko; Dewi Nur Fiana (Medula, 2025)
Hydrocephalus is a condition characterized by the accumulation of cerebrospinal fluid (CSF) within the brain's ventricles, presents a significant challenge in pediatric care. The increased intracranial pressure resulting from this CSF buildup can lead to severe neurological damage if left untreated. Ventricular peritoneal shunt (VP shunt) surgery remains a primary surgical intervention aimed at diverting excess CSF, thereby reducing intracranial pressure and mitigating the risk of irreversible neurological damage. This literature review provides a comprehensive review of the role of VP shunts in the management of pediatric hydrocephalus, encompassing a detailed examination of indications and contraindications for shunt placement, various surgical techniques employed, and the effective management of common post-operative complications such as infection, shunt malfunction (obstruction or overdrainage), and hemorrhage. We meticulously analyze current literature data to assess the effectiveness of VP shunts in improving neurological outcomes, fostering cognitive development, and enhancing the overall quality of life for children affected by hydrocephalus. The analysis will incorporate a review of long-term followup studies to evaluate the durability and efficacy of different shunt types and materials. Case studies and clinical experiences are integrated to provide a nuanced understanding of current clinical practices and to highlight the complexities often encountered in managing this condition. Furthermore, this literature review delves into recent advancements in shunt technology, including the development of programmable valves and less invasive surgical approaches. It also addresses the persistent challenges in optimizing hydrocephalus care, emphasizing the crucial need for a multidisciplinary approach involving neurosurgeons, pediatric neurologists, developmental pediatricians, and other healthcare professionals to ensure holistic and individualized patient care. The ultimate goal is to provide practical, evidence-based guidance for healthcare professionals in the effective and safe management of pediatric hydrocephalus using VP shunts, ultimately improving patient outcomes and quality of life.